When one door closes, another door opens … for some: Evidence from the post‐TRIPS Indian pharmaceutical industry - Chattopadhyay, Shinjinee; Bercovitz, Janet (Strategic Management Journal, 2020)
Abstract Research Summary Firms' strategy choices are contextually dependent, yet internally delimited. A radical shift in institutional context forces firms to reevaluate the desirability and suitability of current strategies and assess the potential of new strategic opportunities. From 1970 to 1995, the Indian pharmaceutical industry operated under a process‐focused intellectual property regime and enjoyed legal protection to reverse engineer brand name drugs. In 1995, this protection ended with the introduction of the trade‐related aspects of intellectual property rights (TRIPS) Act. We examine the innovation response of Indian pharmaceutical firms in light of this regime shift focusing on the underlying internal factors influencing firms' strategic choices. We find that the scope and balance of firms' knowledge bases, which set capabilities and influence decision framing, dictate firms' innovative response. We further document how firms' strategic choices contribute to firm financial performance and the reshaping of the Indian pharmaceutical industry. Managerial Summary From 1970 to 1995, the Indian pharmaceutical industry operated under a process‐focused intellectual property regime and enjoyed legal protection to reverse engineer brand name drugs. Following TRIPS in 1995, the intellectual property regime in India became stronger, with product patent enforcement being recognized. Indian pharmaceutical firms had to make strategic choices on the kind of innovation they would pursue under this new IP regime. This article shows that having broad and nonspecialized knowledge assets allowed firms to pursue the most novel innovation and engage in new product development. Having T‐shaped assets, that is, broad knowledge scope yet narrowly focused knowledge expertise, allowed firms to pursue process‐based innovation in areas close to their existing areas of expertise but not necessarily engage in new product development. The findings of this article shed light on what kind of knowledge base and workforce allows firms to adjust to technological and contextual changes.